A numerical simulation study of methane hydrate reformation during the dissociation process induced by depressurization. (1st April 2022) - Wang, Zhiqiang; Liu, Shuyang; Li, Hangyu; Li, Shuxia; Xu, Jianchun; Wang, Xiaopu
Highlights: Hydrate reformation occurs mainly near the production well because of the insufficient heat supply. The local effective permeability decreases by 13% when the maximum secondary hydrate forms. The cooling driving force is the main controlling mechanism of hydrate reformation during the dissociation process. Production pressure should be controlled subtly to prevent the hydrate reformation. Abstract: Hydrate reformation could impact the gas and water production of hydrate reservoirs especially when it happens near the production wellbore. In this work, a coupled thermal–hydraulic-chemical (THC) model is applied to investigate the characteristics and driving forces of hydrate reformation during the dissociation process induced by depressurization. The results show that hydrate reformation occurs mainly near the production well because of the insufficient heat supply from the ambient environment. The local effective permeability decreases by 13% when the maximum secondary hydrate forms in the base case. The P-T path on the standard hydrate equilibrium curve is an effective method to study the hydrate dissociation or reformation process. The cooling driving force is the main controlling mechanism of hydrate reformation during the dissociation process induced by depressurization. Based on the analysis of the controlling factors, higher intrinsic permeability or lower production pressure results in earlier and larger-scale reformation of secondary hydrate; higher initial hydrate saturation results in later reformation of secondary hydrate. Therefore, the production pressure should be controlled subtly to attain a high gas production rate and prevent the hydrate reformation simultaneously. Hot brine injection or wellbore heating is suggested to eliminate the secondary hydrate near the wellbore.